(untitled) (African Journal of Biomedical Research, 2024)
Cefotaxime is a critically important antimicrobial agent for the treatment of infections in humans and animals. The upsurge in the incidence of cefotaxime-resistant Escherichia coli from animal sources is of global public health importance. Avian pathogenic Escherichia coli is a Gram negative zoonotic bacterial pathogen. Infections by Escherichia coli usually occur following consumption of foods and water contaminated with faeces. The development of antimicrobial resistance in Escherichia coli is a concern worldwide. This study evaluated the prevalence, antimicrobial susceptibility and cefotaxime resistant Escherichia coli in commercial laying hens, indigenous ducks and chickens in Ibadan, Nigeria. Cefotaxime resistant Escherichia coli isolates from the cloacae of these poultry sources were tested for antimicrobial agents. The overall isolation rate of cefotaxime resistant Escherichia coli was 6.5% (6/93), 3.2% (3/93) and 10.0% (20/200) from indigenous ducks, indigenous chickens and commercial laying hens respectively. Cefotaxime resistant Escherichia coli isolates were 89.7%, 86.2%, 65.5%, 55.2%, 37.9%, 27.6%, 20.7% and 20.7% resistant to sulphamethoxazole, tetracycline, ceftazidime, amoxicillin -clavulanic acid, chloramphenicol, ciprofloxacin, gentamicin and ceftriaxone respectively. Whereas, 75.9%, 68.9%, 62.1%, 51.7%, 41.4%, 27.6%,10.3% and 10.3% susceptible to ceftriaxone, ciprofloxacin, gentamicin, chloramphenicol, amoxicillin-clavulanic acid, ceftazidime, sulphamethoxazone and tetracycline respectively. Multidrug resistant (MDR) was observed in 89.7% (26/29) of the isolates which exhibited 2 (in indigenous ducks), 3 (in indigenous chickens) and 13 (in commercial laying hens) different MDR patterns to 7 antimicrobial classes of drug. Higher isolation rate of cefotaxime resistant Escherichia coli and remarkable numbers of the isolates from commercial laying hens showed multidrug resistant than that of indigenous ducks and chickens. Misused of drugs was predicted in commercial laying hens. This study showed that the indigenous ducks and chickens harbour multidrug resistant Escherichia coli and may contribute to environmental contamination through faecal shedding